Small states and the 'throughput' legitimacy of international organizations. Issue 2 (4th March 2018) - Corbett, Jack; Yi-Chong, Xu; Weller, Patrick
Abstract: The unequal participation of member states in international organizations (IOs) undermines IOs' legitimacy as global actors. Existing scholarship typically makes this assessment by referencing a combination of input—the interests IOs serve—and output—the decisions they take. This scholarship does not, however, pay enough attention to how IOs have responded to these concerns. We argue that IOs have used the participation of small states—whose membership most studies typically ignore—as an important means of generating what Vivian Schmidt calls 'throughput' legitimacy for their operations. We organize our analysis of 'throughput' legitimacy in IOs around four institutional mechanisms—(1) agenda setting; (2) leadership (s)election; (3) management and operation; and (4) service delivery—in which all states seek to exert influence. What emerges is an account of IOs seeking to balance 'inputs' and 'outputs' by way of 'throughputs'. We conclude by arguing for an expanded focus on the means by which IOs generate 'throughput' legitimacy in future research.